Pengembangan Modul Pembelajaran Astronomi Mata Pelajaran Tata Surya Terintegrasi dengan Video Augmented Reality - Arif Rahman Aththibby; Friska Octavia Rosa; Nurul Farida; Eko Prihandono (Jurnal Penelitian Pendidikan IPA, 2024)
The rapid development of science and technology makes the teaching and learning process easier. In using technology, media is needed that can provide practicality in supporting learning. The aim of this research is to develop learning media in the form of an integrated Augmented Reality (AR) module for learning physics on the topic of the solar system. Objective: This research develops learning media in the form of modules that are integrated with Augmented Reality (AR) in physics learning on the topic of the solar system. Method: Development research by following Level 1 R&D Research Steps. With minimum standards for good/feasible product validation. As a result of the development results, the module is worthy of being viewed from the media and the context of the content of the solar system material. Apart from that, supporting applications that are capable of producing augmented reality based animations are also feasible both in terms of image selection so that the resulting animations are also in the feasible category. In terms of use, the integrated augmented reality module in physics learning has the potential to improve the quality of student learning